Low-Tube-Voltage Selection for Triple-Rule-Out CTA: Relation to Patient Size - Takx, Richard A. P.; Kriššák, Radko; Fink, Christian; Bachmann, Valentin; Henzler, Thomas; Meyer, Mathias; Schönberg, Stefan; Apfaltrer, Paul (European radiology, 2017)
ObjectivesTo investigate the relationship between image quality and patient size at 100 kilovoltage (kV) compared to 120 kV ECG-gated Triple-Rule-Out CT angiography (TRO-CTA).MethodsWe retrospectively included 73 patients (age 64 ± 14 years) who underwent retrospective ECG-gated chest CTA. 40 patients were scanned with 100 kV while 33 patients with 120 kV. Body mass index (BMI), patients’ chest circumference (PC) and thoracic surface area (TSA) were recorded. Quantitative image quality was assessed as vascular attenuation in the ascending aorta (AA), pulmonary trunk (PA) and left coronary artery (LCA) and the signal-to-noise ratio (SNR) in the AA.ResultsThere was no significant difference in BMI (26.0 ± 4.6 vs. 28.0 ± 6.7 kg/m2), PC (103 ± 7 vs. 104 ± 10 cm2) and TSA (92 ± 15 vs. 91 ± 19 cm2) between 100 kV and 120 kV group. Mean vascular attenuation was significantly higher in the 100 kV compared to the 120 kV group (AA 438 vs. 354 HU, PA 460 vs. 349 HU, LCA 370 vs. 299 HU all p < 0.001). SNR was not significantly different, even after adjusting for patient size. Radiation dose was significantly lower in the 100 kV group (10.7 ± 4.1 vs. 20.7 ± 10.7 mSv; p < 0.001).Conclusions100 kV TRO-CTA is feasible in normal-to-overweight patients while maintaining image quality and achieving substantial dose reduction. Key Points • 100 kV protocols result in a significantly lower radiation dose. • Mean vascular attenuation is significantly higher using 100 kV. • SNR and CNR are not significantly different between 100 kV and 120 kV. • 100 kV CTA is feasible regardless of patient size while maintaining image quality.